2009
DOI: 10.1002/eat.20686
|View full text |Cite
|
Sign up to set email alerts
|

The changing profile of eating disorders at a tertiary psychiatric clinic in Hong Kong (1987–2007)

Abstract: The clinical profile of eating disorders in Hong Kong has increasingly conformed to that of Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 27 publications
3
35
3
Order By: Relevance
“…The higher prevalence of binge eating reported by Singaporean women in this study is somewhat counter-intuitive, given that BN has been observed only rarely in newly industrialized Asian countries and binge eating disorder has not yet been described. 11,36 One possible interpretation of this finding is that there may be a lower threshold for reporting either consumption of ''an unusually large amount of food given the circumstances'' or ''a sense of having lost control over your eating'' among Singaporean women, given the importance placed on self-control, avoidance of shame, and conformity to social norms in traditional Asian societies. 19,37 A lower threshold of this kind would be consistent with Singaporean women's greater fearfulness surrounding weight gain, loss of control over eating, and the prospect of regular weighing.…”
Section: Discussionmentioning
confidence: 92%
“…The higher prevalence of binge eating reported by Singaporean women in this study is somewhat counter-intuitive, given that BN has been observed only rarely in newly industrialized Asian countries and binge eating disorder has not yet been described. 11,36 One possible interpretation of this finding is that there may be a lower threshold for reporting either consumption of ''an unusually large amount of food given the circumstances'' or ''a sense of having lost control over your eating'' among Singaporean women, given the importance placed on self-control, avoidance of shame, and conformity to social norms in traditional Asian societies. 19,37 A lower threshold of this kind would be consistent with Singaporean women's greater fearfulness surrounding weight gain, loss of control over eating, and the prospect of regular weighing.…”
Section: Discussionmentioning
confidence: 92%
“…Self-vomiting, abuse of laxatives and excessive exercise are common compensatory purging mechanisms used in patients with BN (American Psychiatric Association, 1994). The gender difference in both AN and BN is similar with a marked female predominance (Chisuwa and O'Dea, 2010;Lee et al, 2010;Marques et al, 2011;Chandra et al, 2012). Although the etiology of eating disorders has yet to be examined, it is evident that the causes are multifactorial, and are influenced by multiple developmental, social, and biological processes (Kim, 2012;Södersten et al, 2006;Weiselberg et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…This difference may not have had much impact on the findings of this study. Recent studies identified that the eating disorder psychopathology was similar between westernised Chinese and Australians [49,50], and the clinical presentation of eating disorders in Hong Kong Chinese has increasingly been found to conform to that in Western countries [51]. …”
Section: Discussionmentioning
confidence: 99%